2017
DOI: 10.1089/tmj.2016.0048
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for All-Cause Rehospitalization Among Medicare Recipients with Heart Failure Receiving Telehomecare

Abstract: The risk factors identified from this study may be used to drive more effective telehomecare placements, and referrals for additional services among telehomecare patients with HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…In a study of 526 HF patients receiving telehomecare, the researchers identified that 80% of the hospital readmissions could be accounted for by the following five reasons: HF, other heart disease, respiratory infection, cardiac dysrhythmia, and other respiratory problem. 23 Similarly, Thomason et al reported that four out of the seven hospital readmissions, or 57%, among 70 HF patients receiving telehomecare, were due to exacerbation of HF symptoms. 24 Three studies by Madigan and colleagues further shed light on diagnostic reasons for hospital readmissions among HF patients.…”
Section: Reasons For Readmissionsmentioning
confidence: 96%
See 4 more Smart Citations
“…In a study of 526 HF patients receiving telehomecare, the researchers identified that 80% of the hospital readmissions could be accounted for by the following five reasons: HF, other heart disease, respiratory infection, cardiac dysrhythmia, and other respiratory problem. 23 Similarly, Thomason et al reported that four out of the seven hospital readmissions, or 57%, among 70 HF patients receiving telehomecare, were due to exacerbation of HF symptoms. 24 Three studies by Madigan and colleagues further shed light on diagnostic reasons for hospital readmissions among HF patients.…”
Section: Reasons For Readmissionsmentioning
confidence: 96%
“…Half (n = 9) of the reviewed studies focused on patients with heart failure (HF). Of these studies, there were six on HF patients receiving regular home care, [16][17][18][19][20][21] two on HF patients receiving telehomecare, 22,23 and one study on HF patients receiving either regular home care or telehomecare. 24 The other studies covered a variety of HHC patients with seven (39%) focused on general home care patients, [25][26][27][28][29][30][31] one (6%) focused on patient with diabetes, 32 and one (6%) focused on children.…”
Section: Quality Appraisal Of Reviewed Studiesmentioning
confidence: 99%
See 3 more Smart Citations